The Influence of Geographical Origin on Poplar Propolis Composition and the Impact of Human Microbiota - Michał Miłek; Gabriela Franke; Monika Tomczyk; Miłosz Górecki; Olga Cwiková; Alžbeta Jarošová; Małgorzata Dżugan (MDPI AG, 2024)
Ethanol extracts obtained from 13 poplar propolis samples originating from various European countries by traditional maceration were tested for total polyphenols, flavonoid content, and antioxidant activity. Moreover, the content of 18 polyphenolic compounds (from the group of phenolic acids and flavonoids) was determined using the HPLC method. The inhibitory effect of six selected extracts with the highest activity was assessed by well-diffusion method against five strains (Bifidobacterium spp., L. rhamnosus, L. acidophilus, E. coli, and Bacteroides spp.) of intestinal bacteria self-isolated from the faeces of obese probands with the use of selective media. It was found that the antioxidant activity of propolis varied depending on geographical origin and even among samples from the same region, which indicates that some other factors also influence propolis quality. The samples of different geographical origin varied mainly in the share of individual phenolic compounds, and it was not possible to find a characteristic marker of origin, excluding the galangin present in the Polish samples only. Assessing the inhibitory activity of propolis (in the range of 70 mg to 10 µg per mL) indicated that the concentration of 100 µg/mL was found as being safe for tested fecal bacteria (Bifidobacterium spp., L. rhamnosus, L. acidophilus, E. coli, and Bacteroides spp.). As no negative effect of low doses of propolis on the intestinal microflora was found, it can be suggested that its use in recommended doses brings only beneficial effects to the body.